Analisis Temperatur Pada Proses Extruding Pelet Apung - Darianto Darianto; Amirsyam Nasution; Muhammad Idris (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2021)
Extruder is a device that consists of a screw (a type of pressure screw), the thread functions as a propulsion and presses the raw material so that it turns into a semi-solid material. The material is pushed and pressed out through a confined hole (die) at the thread end. The heater gives heat to the material being extruded which is called hot extrusion. The cutting knife is used to even out the size of the extruded cut, and the main feature of the extrusion process is its continuous nature. The extruder is operated under conditions of dynamic equilibrium, that is, the input equals the output, the incoming material is equivalent to the product.